2003
DOI: 10.1111/j.1550-7408.2003.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Four Human Microsporidian Isolates by MALDI‐TOF Mass Spectrometry

Abstract: Spores of four species of microsporidia isolated from humans were analyzed by matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) and specific biomarkers were found for each. The microsporidia analyzed included three species, Encephalitozoon cuniculi, Encephalitozoon hellem, and Encephalitozoon intestinalis and the fourth organism is the recently described Brachiola algerae. Whole spores, spore shells, and soluble fractions were applied directly to the MALDI target witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…Additionally, Shaw et al reported the identification of biomarkers in unfractionated C. burnetii cells phase I purified from embryonic egg yolk sac preparations (24). Furthermore, spectral markers in the mass range of 2,000 to 8,000 Da were obtained from MALDI-TOF MS analysis of four human microsporidian isolates (16). Biomarkers for Mycobacterium species have also been detected by MALDI primarily in the 500-to 2,000-Da range, most likely representing lipid molecules or small polypeptides (18).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Shaw et al reported the identification of biomarkers in unfractionated C. burnetii cells phase I purified from embryonic egg yolk sac preparations (24). Furthermore, spectral markers in the mass range of 2,000 to 8,000 Da were obtained from MALDI-TOF MS analysis of four human microsporidian isolates (16). Biomarkers for Mycobacterium species have also been detected by MALDI primarily in the 500-to 2,000-Da range, most likely representing lipid molecules or small polypeptides (18).…”
Section: Discussionmentioning
confidence: 99%
“…The results of MALDI-TOF MS analysis provide similar to those obtained by genetic molecular analysis and the outcome of MALDI-TOF MS identification is comparable to and as reliable as that originating from established genetic methods (e.g., Caldwell, and Caprioli 2005). These advantages did stimulate a number of studies addressed to improve the effectiveness of this application on whole microorganisms (Claydon et al 1996;Demirev et al 2001;Moura et al 2003;Hettick et al 2004) and on target organs and tissues of animals in ecotoxicology, neurophysiology and food control (e.g., Neupert, and Predel 2005;Mezhoud et al 2008;Keyvanshokooh et al 2009;Lu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was shown that incubation of intact oocytes and purified sporozoites for 45 min with the matrix was critical for generating mass spectra with a large number of reproducible peaks for C. parvum oocysts (Glassmeyer et al, 2007). Subsequently, direct application of whole spores, spore shells, and soluble fractions of spore-forming unicellular parasites such as microsporidia, Encephalitozoon cuniculi, Encephalitozoon hellem, Encephalitozoon intestinalis , and Brachiola algerae isolated from humans and propagated on monolayers of Vero monkey kidney (E6) cells, displayed species-specific markers in the mass range of 2,000–8,000 Da (Moura et al, 2003). Later, species-specific peaks in the range of m/z 3,000–19,000 was reported for the water-borne protozoan parasite, Giardia spp., the causative agent of giardiasis.…”
Section: Advances In Invertebrate Pests Parasite and Vector Profilingmentioning
confidence: 99%